Chronic Overexpression of Bradykinin in Kidney Causes Polyuria and Cardiac Hypertrophy - Barros, Carlos C.; Schadock, Ines; Sihn, Gabin; Rother, Franziska; Xu, Ping; Popova, Elena; Lapidus, Irina; Plehm, Ralph; Heuser, Arnd; Todiras, Mihail; Bachmann, Sebastian; Alenina, Natalia; et al. (Frontiers in Medicine, 2018)
Acute intra-renal infusion of bradykinin increases diuresis and natriuresis via inhibition of vasopressin activity. However, the consequences of chronically increased bradykinin in the kidneys have not yet been studied. A new transgenic animal model producing an excess of bradykinin by proximal tubular cells (KapBK rats) was generated and submitted to different salt containing diets to analyze changes in blood pressure and other cardiovascular parameters, urine excretion and composition, as well as levels and expression of renin-angiotensin system components. Despite that KapBK rats excrete more urine and sodium, they have similar blood pressure as controls with the exception of a small increase in systolic blood pressure. However, they present decreased renal artery blood flow, increased intrarenal expression of angiotensinogen and decreased mRNA expression of vasopressin V1A receptor (AVPR1A), suggesting a mechanism for the previously described reduction of renal vasopressin sensitivity by bradykinin. Additionally, reduced heart rate variability, increased cardiac output and frequency, and the development of cardiac hypertrophy are the main chronic effects observed in the cardiovascular system. In conclusion: 1) the transgenic KapBK rat is a useful model for studying chronic effects of bradykinin in kidney; 2) increased renal bradykinin causes changes in renin angiotensin system regulation; 3) decreased renal vasopressin sensitivity in KapBK rats is related to decreased V1A receptor expression; 4) although increased renal levels of bradykinin causes no changes in mean arterial pressure, it causes reduction in heart rate variability, augmentation in cardiac frequency and output and consequently cardiac hypertrophy in rats after 6 months of age.